Sekolah Ramah Anak Sebagai Perwujudan Harapan Bangsa - Dian Purbo Ningrum; Nur Afif Wahyudin; Rifana Intan Fauziyah; Vika Yulia Safitri; Muhammad Nofan Zulfahmi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This research was conducted to find out about "child-friendly schools in elementary schools". The purpose of the research is to guarantee efforts to fulfill children's rights and minimize the occurrence of acts of violence against children and provide quality education for children. This study uses a type of qualitative research. The method used in this study uses a library research method or approach. The data collection technique used in this article is to review journals, books, and literature articles that are appropriate to the research problem. The findings from the data collection process are documented to then be analyzed and presented descriptively. The hopes to be achieved from this research are 1.) to be able to find out the effectiveness of child-friendly schools in realizing the hopes of the nation. 2.) aims to provide strengthening, understanding and instilling and implementing Pancasila values. 3.) provide knowledge and understanding to children/students to practice and implement Pancasila values.